2017
DOI: 10.1103/physreve.96.013104
|View full text |Cite
|
Sign up to set email alerts
|

Apparent slip of shear thinning fluid in a microchannel with a superhydrophobic wall

Abstract: The peculiarities of simple shear flow of shear thinning fluids over a superhydrophobic wall consisting of a set of parallel gas-filled grooves and solid stripes (domains with slip and stick boundary conditions) are studied numerically. The Carreau-Yasuda model is used to provide further insight into the problem of the slip behavior of non-Newtonian fluids having a decreasing viscosity with a shear rate increase. This feature is demonstrated to cause a nonlinear velocity profile leading to the apparent slip. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…As can be seen in previous sections, the friction factor ratio was noticed to be minimized for the shear-thinning liquids at certain shear rates. Some of the previous research also reported that the hydrodynamic drag minimises on the SH textures when shear-thinning liquids are employed (Haase et al 2017;Patlazhan and Vagner 2017;Crowdy 2017). It is well-accepted that the reduction in hydrodynamic friction for a flow of shear-thinning liquid is attributed to the depletion layer near the wall having considerably less viscosity than the bulk liquid as shown in Fig.…”
Section: Discussion On Minima Of the Friction Factor Ratiomentioning
confidence: 81%
See 3 more Smart Citations
“…As can be seen in previous sections, the friction factor ratio was noticed to be minimized for the shear-thinning liquids at certain shear rates. Some of the previous research also reported that the hydrodynamic drag minimises on the SH textures when shear-thinning liquids are employed (Haase et al 2017;Patlazhan and Vagner 2017;Crowdy 2017). It is well-accepted that the reduction in hydrodynamic friction for a flow of shear-thinning liquid is attributed to the depletion layer near the wall having considerably less viscosity than the bulk liquid as shown in Fig.…”
Section: Discussion On Minima Of the Friction Factor Ratiomentioning
confidence: 81%
“…16a. Consequently, Patlazhan and Vagner (2017) showed that the ratio Fig. 11 The shear rate (top panel) and viscosity (bottom panel) distribution on the bottom wall at different Carreau numbers for a flow past single post in a microchannel with HL = 0.5.…”
Section: Discussion On Minima Of the Friction Factor Ratiomentioning
confidence: 99%
See 2 more Smart Citations
“…The slip length can be interpreted as the distance from the wall that the slip velocity profile extends to if extrapolated away from the boundary. In gas flows, the slip length is related to the Knudsen number, while in liquid flows, the slip length depends on the surface microstructure [27,28,29,30,31,32,33,34,35,36,37]. When considering liquids, the molecular mean free path may be replaced by the slip length and the Knudsen number may be replaced by the modified Knudsen number.…”
Section: Literature Reviewmentioning
confidence: 99%